Physical Vapor Deposited TiN and TiAlN on Biomedical β-Type Ti-29Nb-13Ta-4.6Zr: Microstructural Characteristics, Surface Hardness Enhancement, and Antibacterial Activity - Yilmazer, Hakan (MDPI, 2025)
Beta (beta)-type Ti-29Nb-13Ta-4.6Zr (TNTZ) alloys combine low modulus with biocompatibility but require improved surface properties for long-term implantation. This study aimed to enhance the surface mechanical strength and antibacterial performance of TNTZ by applying TiN and TiAlN coatings via PVD. Notably, TiAlN was deposited on TNTZ for the first time, enabling a direct side-by-side comparison with TiN under identical deposition conditions. Dense TiN (similar to 1.06 mu m) and TiAlN (similar to 1.73 mu m) coatings were deposited onto solution-treated TNTZ and characterized by X-ray diffraction, scanning probe microscopy, Vickers microhardness, Rockwell indentation test (VDI 3198), static water contact angle measurements, and a Kirby-Bauer disk-diffusion antibacterial assay against Escherichia coli (E. coli). Both coatings formed face-centered cubic (FCC) structures with smooth interfaces (Ra 0.05), indicating that only a preliminary bacteriostatic trend- rather than a definitive antibacterial effect-was observed. Both nitride coatings strengthened TNTZ without compromising its structural integrity, making TiAlN-coated TNTZ a promising candidate for next-generation orthopedic implants.
Keywords: biomedical beta-type titanium alloys; thin film coatings (TiN and TiAlN); physical vapor deposition (PVD); TITANIUM-ALLOYS; BACTERIAL ADHESION; MECHANICAL-PROPERTIES; CUTTING PERFORMANCE; CELL VIABILITY; SINGLE-LAYER; COATINGS; BEHAVIOR; BONE; STABILITY; Materials Science; Physics